Evaluation of Immune Survival Factors in Pediatric HIV-1 Infection - SHEARER, WILLIAM T. (Ann N Y Acad Sci, 2000)
Peripheral blood CD4(+) and CD8(+) T cells, CD19(+)/20(+) B cells, and serum immunoglobulins (Igs) have been implicated as survival factors for pediatric HIV-1 infection. To determine which of these immune factors might be important in predicting survival, we studied HIV-1 vertically infected (HIV-1(+)) children over a 5-year period. Peripheral blood lymphocytes and Igs were measured in 298 HIV-1(+) children, who were classified as survivors or nonsurvivors, and in 463 HIV-1 vertically exposed and noninfected (HIV-1(–)) children. Measurements of other possible survival factors were included in this study: albumin, hemoglobin, lactic dehydrogenase (LDH), and HIV-1 RNA levels. Survivors had significantly higher CD4(+) T-cell, CD8(+) T-cell, and CD19(+)/CD20(+) B-cell counts and serum IgG levels, but lower serum IgA and IgM levels than nonsurvivors. Serum albumin and blood hemoglobin levels were higher, but serum LDH and HIV-1 RNA levels were lower in the survivors compared to non-survivors. In univariable analysis, factors affecting survival were baseline CD4(+) T-cell and CD8(+) T-cell counts, IgG, albumin, hemoglobin, LDH, and HIV-1 RNA (all p < 0.001). In multivariable analysis, high baseline CD4(+) T-cell count, IgG and albumin levels, and low baseline HIV-1 RNA load remained important factors for survival. Serum IgG level has been identified as an immune factor that independently predicts survival, in addition to the already established CD4(+) T-cell count. The HIV-1 RNA and serum albumin levels also predicted survival.